We need land first: Identifying local needs for sustainable recovery after the 2015 Gorkha earthquake, Nepal - Lulu He (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The aim of this study is to identify needs for recovery from people's perspectives under a localized context following the 2015 earthquake in Nepal. A qualitative approach was applied to collecting and processing data which consist of 114 semi-structured interviews with earthquake-resettled households, six focus group discussions, interviews with community leaders and government officials, and participant observations. Data suggest that recovery needs at local communities are sustainable because the affected population is more concerned about productive living and development issues rather than physical reconstruction. While building new houses appears to be the most urgent task, people wish to have permanent ownership of land at a different place for reconstruction, and to gain employability for overseas job-hunting. These needs are interlinked, and the interlinkage is manifested in the reliance on the central authority to take action. These findings imply that comprehensive recovery from the earthquake calls for reconstruction in multiple sectors.
Keywords: Q54; H12; Y80; 330; post-disaster needs assessment (PDNA); sustainability; community recovery; resettled households; earthquake; Nepal